Sealing agent for liquid crystal element
By adding a thermal polymerization initiator and a cyano initiator to the sealant of the liquid crystal element, the liquid crystal pollution and peeling problems caused by insufficient photocuring are solved, and efficient thermal curing and anti-peeling effects are achieved at low temperatures.
Patent Information
- Application Number
- CN202411227893.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-28
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-04
AI Technical Summary
In the narrow frame design, the sealant is not cured sufficiently, resulting in liquid crystal contamination and peeling problems after curing.
The thermal polymerization initiator is combined with the sealant to rapidly heat cure the part that is not cured under light irradiation, and azo initiator with a cyano group is used to improve the reaction efficiency and optimize the composition of the curable resin and the thermal curing agent.
Low liquid crystal contamination during thermal curing at low temperature and anti-peeling effect after curing, ensuring high quality and stability of liquid crystal components.
Smart Images

Figure BDA0005025201230000101 
Figure BDA0005025201230000191 
Figure BDA0005025201230000201
Abstract
Description
Technical Field
[0001] The present invention relates to a sealing agent for a liquid crystal element which is excellent in low liquid crystal contamination property when thermally cured at a low temperature and can suppress peeling after curing. Background Art
[0002] In recent years, as a method for manufacturing liquid crystal elements, from the viewpoints of shortening the production cycle time and optimizing the amount of liquid crystal used, a liquid crystal dropping method called a dropping process as disclosed in Patent Documents 1 and 2 has been used. This dropping process uses a photothermal curing sealant containing a curable resin, a photopolymerization initiator and a thermosetting agent.
[0003] In the dripping process, first, a rectangular seal pattern is formed on one of the two substrates with electrodes by dispensing. Next, tiny drops of liquid crystal are dripped into the sealing frame of the substrate while the sealant is not cured, and the other substrate is overlapped under vacuum, and the seal is irradiated with light such as ultraviolet rays for pre-curing. After that, it is heated for main curing to produce a liquid crystal element. At present, this dripping process has become the mainstream method for manufacturing liquid crystal elements.
[0004] However, in the modern era when various mobile devices with liquid crystal panels such as mobile phones and portable game consoles are popular, miniaturization of devices is the most needed issue. As a method for miniaturization of devices, narrow frame of liquid crystal display part can be cited, for example, a design in which the sealing part is arranged under the black matrix (hereinafter also referred to as narrow frame design) is performed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2001-133794
[0008] Patent document 2: International Publication No. 02 / 092718 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In the narrow frame design, since the sealant is arranged directly below the black matrix, if the dripping process is performed, the light irradiated when the sealant is photocured is blocked, and the light is difficult to reach the inside of the sealant, and the conventional sealant curing becomes insufficient. If the sealant curing becomes insufficient as described above, there is a problem that the uncured sealant components are eluted into the liquid crystal, which is easy to cause liquid crystal contamination.
[0011] Therefore, the following research has been conducted: by adding a thermal polymerization initiator to the sealant, the portion that is not sufficiently cured under light irradiation is quickly thermally cured, thereby suppressing liquid crystal contamination. In the case of heating at a low temperature in consideration of damage to the liquid crystal element, ECO activity, etc., if the reaction efficiency of the thermal polymerization initiator is low, it is difficult to fully thermally cure the portion that is not sufficiently cured under light irradiation, so an azo initiator having a cyano group is used as a thermal polymerization initiator with high reaction efficiency at low temperatures. However, when such a thermal polymerization initiator is used, the cured product of the obtained sealant becomes too hard, and the stress when the multiple units formed on the mother glass are divided cannot be relieved, and the stress caused by the vibration during transportation cannot be relieved, etc., and sometimes peeling occurs on the substrate.
[0012] An object of the present invention is to provide a sealing agent for a liquid crystal element which is excellent in low liquid crystal contamination property when thermally cured at a low temperature and can suppress peeling after curing.
[0013] Means for solving problems
[0014] The present invention 1 relates to a sealing agent for a liquid crystal element, which contains a curable resin, a thermal polymerization initiator, a photopolymerization initiator and a thermal curing agent, wherein the curable resin contains a (meth)acrylic compound and an epoxy compound, the (meth)acrylic compound contains a compound having three or more (meth)acryloyl groups in one molecule, and the thermal polymerization initiator is an azo compound having a cyano group and an azo group, at least one of the cyano group and at least one of the azo group are bonded to the same carbon atom, and the carbon atom bonded to the at least one cyano group and at least one of the azo group is also bonded to a linear or branched organic group having three or more carbon atoms.
[0015] Invention 2 relates to the sealing agent for liquid crystal elements of invention 1, wherein the (meth)acrylic compound includes a compound having four or more (meth)acryloyl groups in one molecule.
[0016] The present invention 3 relates to the sealing agent for liquid crystal elements of the present invention 1 or 2, wherein the linear or branched organic group having 3 or more carbon atoms contains one or more oxygen atoms.
[0017] Invention 4 relates to the sealing agent for liquid crystal elements of invention 1, 2 or 3, wherein the linear or branched organic group having 3 or more carbon atoms contains at least one polar group selected from the group consisting of a carboxyl group, an ester bond and an ether bond.
[0018] The present invention 5 is related with the sealing agent for liquid crystal elements of the present invention 1, 2, 3 or 4, wherein the cured product of the sealing agent for liquid crystal elements has a Martens hardness of 180 MPa or less when measured by a nanoindenter.
[0019] The present invention 6 relates to the sealing agent for liquid crystal elements of the present invention 1, 2, 3, 4 or 5, wherein the indentation hardness of the cured product of the sealing agent for liquid crystal elements measured by a nanoindenter is 30 MPa or less.
[0020] Hereinafter, the present invention will be described in detail.
[0021] The present inventors have studied the following scheme: in a liquid crystal element sealant containing a curable resin, a thermal polymerization initiator, a photopolymerization initiator and a thermal curing agent, compounds having specific structures are used in combination as the curable resin and the thermal polymerization initiator. As a result, it was found that a liquid crystal element sealant having excellent low liquid crystal contamination during thermal curing at low temperature and capable of suppressing peeling after curing can be obtained, thereby completing the present invention.
[0022] The sealing agent for liquid crystal elements of the present invention contains a curable resin.
[0023] The curable resin includes a (meth)acrylic compound and an epoxy compound.
[0024] In addition, in this specification, the said "(meth)acrylic acid" means acrylic acid or methacrylic acid.
[0025] The (meth)acrylic compound includes a compound having three or more (meth)acryloyl groups in one molecule (hereinafter also referred to as a "trifunctional or higher-functional (meth)acrylic compound"). By using the trifunctional or higher-functional (meth)acrylic compound in combination with the thermal polymerization initiator of the present invention described below, the sealing agent for liquid crystal elements of the present invention is excellent in low liquid crystal contamination during thermal curing at low temperature and can suppress peeling after curing.
[0026] In addition, in this specification, the said "(meth)acryloyl group" means an acryloyl group or a methacryloyl group.
[0027] Examples of the trifunctional or higher-functional (meth)acrylic compound include ethylene oxide-added isocyanuric acid tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ethylene oxide-added trimethylolpropane tri(meth)acrylate, propylene oxide-added trimethylolpropane tri(meth)acrylate, caprolactone-modified trimethylolpropane tri(meth)acrylate, glycerol tri(meth)acrylate, propylene oxide-added glycerol tri(meth)acrylate, pentaerythritol tri(meth)acrylate, tri(meth)acryloyloxyethyl phosphate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.
[0028] Among them, from the viewpoint of making the obtained sealing agent for liquid crystal elements a sealing agent with better low liquid crystal contamination properties, the above-mentioned (meth)acrylic compound preferably contains a compound having 4 or more (meth)acryloyl groups in one molecule as the above-mentioned trifunctional or higher-functional (meth)acrylic compound.
[0029] In addition, in this specification, the said "(meth)acrylate" means acrylate or methacrylate.
[0030] Examples of commercially available products among the trifunctional or higher-functional (meth)acrylic compounds include M-315 (manufactured by Toagosei Co., Ltd.) and A-DPH (manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0031] The preferred lower limit of the content of the above-mentioned trifunctional or higher (meth) acrylic acid compound in 100 parts by mass of the above-mentioned curable resin is 5 parts by mass, and the preferred upper limit is 20 parts by mass. By making the content of the above-mentioned trifunctional or higher (meth) acrylic acid compound more than 5 parts by mass, the low liquid crystal contamination of the obtained liquid crystal element sealant during thermal curing at low temperature becomes more excellent. By making the content of the above-mentioned trifunctional or higher (meth) acrylic acid compound less than 20 parts by mass, the stress relaxation of the cured product of the obtained liquid crystal element sealant is more excellent, and peeling can be further suppressed. The more preferred lower limit of the content of the above-mentioned trifunctional or higher (meth) acrylic acid compound is 7 parts by mass, the more preferred upper limit is 18 parts by mass, the further preferred lower limit is 8 parts by mass, and the further preferred upper limit is 17 parts by mass.
[0032] From the viewpoints of low liquid crystal contamination, adhesion, moisture permeation resistance, etc., the curable resin preferably contains another (meth)acrylic compound as the (meth)acrylic compound in addition to the trifunctional or higher-functional (meth)acrylic compound.
[0033] The above-mentioned other (meth)acrylic compounds are compounds having one (meth)acryloyl group in one molecule (hereinafter also referred to as "monofunctional (meth)acrylic compound") or compounds having two (meth)acryloyl groups in one molecule (hereinafter also referred to as "bifunctional (meth)acrylic compound").
[0034] Examples of the monofunctional (meth)acrylic acid compound include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, lauryl (meth)acrylate, isomyristyl (meth)acrylate, stearyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentenyl (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 2-Butoxyethyl (meth)acrylate, 2-phenoxyethyl (meth)acrylate, methoxyethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, phenoxydiethylene glycol (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, ethyl carbitol (meth)acrylate, 2,2,2-trifluoroethyl (meth)acrylate, 2,2,3,3-tetrafluoropropyl (meth)acrylate, 1H,1H,5H-octafluoropentyl (meth)acrylate, imide (meth)acrylate, dimethylaminoethyl (meth)acrylate, diethylaminoethyl (meth)acrylate, 2-(meth)acryloyloxyethyl succinate, 2-(meth)acryloyloxyethyl hexahydrophthalate, 2-(meth)acryloyloxyethyl 2-hydroxypropyl phthalate, 2-(meth)acryloyloxyethyl phosphate, glycidyl (meth)acrylate, and the like.
[0035] Examples of the bifunctional (meth)acrylic compound include bifunctional epoxy (meth)acrylates, bifunctional (meth)acrylate compounds, and bifunctional urethane (meth)acrylates. Among them, bifunctional epoxy (meth)acrylates are preferred.
[0036] In addition, in this specification, the said epoxy (meth)acrylate means the compound which made all the epoxy groups in an epoxy compound react with (meth)acrylic acid.
[0037] Examples of the bifunctional epoxy (meth)acrylate include epoxy (meth)acrylates obtained by reacting a bifunctional epoxy compound with (meth)acrylic acid in the presence of a basic catalyst according to a conventional method.
[0038] Examples of the bifunctional epoxy compound used as a raw material for the bifunctional epoxy (meth)acrylate include bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol S epoxy compounds, 2,2′-diallylbisphenol A epoxy compounds, hydrogenated bisphenol epoxy compounds, propylene oxide-added bisphenol A epoxy compounds, resorcinol epoxy compounds, biphenyl epoxy compounds, thioether epoxy compounds, diphenyl ether epoxy compounds, dicyclopentadiene epoxy compounds, naphthalene epoxy compounds, glycidylamine epoxy compounds, alkyl polyol epoxy compounds, rubber-modified epoxy compounds, and glycidyl ester compounds.
[0039] Examples of the bifunctional (meth)acrylate compound include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, 2-n-butyl-2-ethyl-1,3-propanediol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethylene oxide-added bisphenol A di(meth)acrylate, propylene oxide-added bisphenol A di(meth)acrylate, ethylene oxide-added bisphenol F di(meth)acrylate, dimethylol dicyclopentadienyl di(meth)acrylate, ethylene oxide-modified isocyanuric acid di(meth)acrylate, 2-hydroxy-3-(meth)acryloxypropyl (meth)acrylate, carbonate glycol di(meth)acrylate, polyether glycol di(meth)acrylate, polyester glycol di(meth)acrylate, polycaprolactone glycol di(meth)acrylate, polybutadiene glycol di(meth)acrylate, and the like.
[0040] The bifunctional urethane (meth)acrylate can be obtained, for example, by reacting a (meth)acrylic acid derivative having a hydroxyl group with a bifunctional isocyanate compound in the presence of a catalytic amount of a tin-based compound.
[0041] Examples of the bifunctional isocyanate compound include isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4′-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, dimethylbiphenyl diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, and tetramethylxylylene diisocyanate.
[0042] Furthermore, as the above-mentioned bifunctional isocyanate compound, a chain-extended bifunctional isocyanate compound obtained by reacting a polyol with an excess amount of a bifunctional isocyanate compound may be used.
[0043] Examples of the polyol include ethylene glycol, propylene glycol, glycerin, sorbitol, trimethylolpropane, carbonate diol, polyether diol, polyester diol, and polycaprolactone diol.
[0044] Examples of the (meth)acrylic acid derivative having a hydroxyl group include hydroxyalkyl mono(meth)acrylates, mono(meth)acrylates of diols, and mono(meth)acrylates of triols.
[0045] Examples of the hydroxyalkyl mono(meth)acrylate include 2-hydroxyethyl(meth)acrylate, 2-hydroxypropyl(meth)acrylate, 2-hydroxybutyl(meth)acrylate, and 4-hydroxybutyl(meth)acrylate.
[0046] Examples of the diol include ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,4-butanediol, and polyethylene glycol.
[0047] Examples of the triol include trimethylolethane, trimethylolpropane, and glycerin.
[0048] The curable resin may contain a compound having one or more epoxy groups and one or two (meth)acryloyl groups in one molecule as the other (meth)acrylic compound. Examples of such compounds include partially (meth)acrylic acid-modified epoxy compounds.
[0049] The partially (meth)acrylic acid-modified epoxy compound can be obtained, for example, by reacting one epoxy group of the bifunctional epoxy compound with (meth)acrylic acid.
[0050] When the curable resin includes the other (meth) acrylic compounds, the preferred lower limit of the content of the other (meth) acrylic compounds in 100 parts by mass of the curable resin is 60 parts by mass, and the preferred upper limit is 90 parts by mass. By making the content of the other (meth) acrylic compounds within this range, the low liquid crystal contamination, curability and adhesion of the obtained liquid crystal element sealant become more excellent. The more preferred lower limit of the content of the other (meth) acrylic compounds is 65 parts by mass, and the more preferred upper limit is 85 parts by mass.
[0051] Examples of the epoxy compound contained in the curable resin include bisphenol A epoxy compounds, bisphenol F epoxy compounds, bisphenol S epoxy compounds, 2,2'-diallylbisphenol A epoxy compounds, hydrogenated bisphenol epoxy compounds, propylene oxide-added bisphenol A epoxy compounds, resorcinol epoxy compounds, biphenyl epoxy compounds, sulfide epoxy compounds, diphenyl ether epoxy compounds, dicyclopentadiene epoxy compounds, and the like. Type epoxy compounds, naphthalene type epoxy compounds, phenol novolac type epoxy compounds, o-cresol novolac type epoxy compounds, dicyclopentadiene novolac type epoxy compounds, biphenyl novolac type epoxy compounds, naphthol novolac type epoxy compounds (Japanese: ナフタレンフェノールノボラック type epoxide compounds), glycidylamine type epoxy compounds, alkyl polyol type epoxy compounds, rubber modified epoxy compounds, glycidyl ester compounds, etc.
[0052] The preferred lower limit of the content of the above-mentioned epoxy compound in 100 parts by mass of the above-mentioned curable resin is 5 parts by mass, and the preferred upper limit is 30 parts by mass. By making the content of the above-mentioned epoxy compound within this range, the low liquid crystal contamination, curability and adhesion of the obtained liquid crystal element sealant become more excellent. The more preferred lower limit of the content of the above-mentioned epoxy compound is 10 parts by mass, and the more preferred upper limit is 20 parts by mass.
[0053] The preferred lower limit of the content of the above-mentioned curable resin as a whole in 100 parts by mass of the sealant for liquid crystal cells of the present invention is 60 parts by mass, and the preferred upper limit is 80 parts by mass. By making the content of the above-mentioned curable resin as a whole be within this range, the curability and adhesion of the obtained sealant for liquid crystal cells become more excellent. The more preferred lower limit of the content of the above-mentioned curable resin as a whole is 65 parts by mass, and the more preferred upper limit is 75 parts by mass.
[0054] The sealing agent for liquid crystal elements of the present invention contains a thermal polymerization initiator.
[0055] The thermal polymerization initiator is an azo compound having a cyano group and an azo group. In the azo compound, at least one of the cyano group and at least one of the azo group are bonded to the same carbon atom, and the carbon atom bonded to at least one of the cyano group and at least one of the azo group is also bonded to a linear or branched organic group having 3 or more carbon atoms. Hereinafter, a thermal polymerization initiator containing a compound having carbon atoms bonded to all of a cyano group, an azo group, and a linear or branched organic group having 3 or more carbon atoms is also referred to as a "thermal polymerization initiator according to the present invention".
[0056] By using the thermal polymerization initiator of the present invention in combination with the trifunctional or higher-functional (meth)acrylic compound, the sealing agent for liquid crystal elements of the present invention has excellent low liquid crystal contamination during thermal curing at low temperature and can suppress peeling after curing.
[0057] Furthermore, the thermal polymerization initiator according to the present invention preferably does not have a cyclic skeleton.
[0058] The preferred lower limit of the molecular weight of the thermal polymerization initiator of the present invention is 200, and the preferred upper limit is 300,000. By making the molecular weight of the thermal polymerization initiator of the present invention within this range, the obtained liquid crystal element sealant has a better effect of both low liquid crystal contamination during thermal curing at low temperature and stress relaxation after curing. The more preferred lower limit of the molecular weight of the above-mentioned azo compound is 250, and the more preferred upper limit is 100,000.
[0059] It should be noted that, in this specification, for the compound determined by molecular structure, the above-mentioned molecular weight is the molecular weight obtained by structural formula, but for the compound with wide distribution of polymerization degree and the uncertain compound of modified part, the above-mentioned molecular weight is sometimes represented by weight average molecular weight. In addition, in this specification, the above-mentioned "weight average molecular weight" is the value obtained by polystyrene conversion using tetrahydrofuran as solvent using gel permeation chromatography (GPC). As the column used when measuring the weight average molecular weight converted based on polystyrene by GPC, for example, Shodex LF-804 (Showa Denko Co., Ltd. system) etc. can be cited.
[0060] The linear or branched organic group having 3 or more carbon atoms preferably contains 1 or more oxygen atoms. When the linear or branched organic group having 3 or more carbon atoms contains 1 or more oxygen atoms, the low liquid crystal contamination property of the obtained liquid crystal element sealing agent is further improved.
[0061] In addition, the straight-chain or branched organic group having 3 or more carbon atoms is preferably an organic group containing a polar group. By making the straight-chain or branched organic group having 3 or more carbon atoms an organic group containing a polar group, the low liquid crystal contamination property of the obtained liquid crystal element sealing agent becomes more excellent.
[0062] Among them, the linear or branched organic group having 3 or more carbon atoms more preferably includes at least one polar group selected from the group consisting of a carboxyl group, an ester bond, and an ether bond.
[0063] From the viewpoint of further improving the low liquid crystal contamination property of the obtained sealing agent for liquid crystal elements, the thermal polymerization initiator according to the present invention is preferably a thermal polymerization initiator containing oxygen atoms, and more preferably a thermal polymerization initiator containing 4 or more oxygen atoms in one molecule.
[0064] Among them, as the thermal polymerization initiator of the present invention, from the perspective of achieving a better effect of achieving both low liquid crystal contamination during thermal curing at low temperature and stress relaxation after curing in the obtained liquid crystal element sealing agent, the compound represented by the following formula (1) is preferred, and more preferably at least one selected from 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 4,4'-azobis(4-cyanovaleric acid), and a condensation product of 4,4'-azobis(4-cyanovaleric acid) and polyalkylene glycol.
[0065] [Chemistry 1]
[0066]
[0067] In formula (1), R represents the above-mentioned linear or branched organic group having 3 or more carbon atoms.
[0068] Examples of commercially available products of the thermal polymerization initiator according to the present invention include V-65, V-70, V-501, and VPE-0201 (all manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).
[0069] Relative to 100 parts by mass of the curable resin, the preferred lower limit of the content of the thermal polymerization initiator according to the present invention is 0.1 parts by mass, and the preferred upper limit is 30 parts by mass. By making the content of the thermal polymerization initiator according to the present invention within this range, the effect of the obtained liquid crystal element sealant in terms of both low liquid crystal contamination during thermal curing at low temperatures and stress relaxation after curing becomes more excellent. The more preferred lower limit of the thermal polymerization initiator according to the present invention is 0.5 parts by mass, and the more preferred upper limit is 10 parts by mass.
[0070] The sealing agent for liquid crystal elements of the present invention contains a photopolymerization initiator.
[0071] Examples of the photopolymerization initiator include benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone compounds.
[0072] Specific examples of the photopolymerization initiator include 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-(dimethylamino)-2-((4-methylphenyl)methyl)-1-(4-(4-morpholino)phenyl)-1-butanone, 2,2-dimethoxy-1,2-diphenylethane-1-one, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2-methyl-1-(4-methylthiophene). phenyl)-2-morpholinopropane-1-one, 1-(4-(2-hydroxyethoxy)-phenyl)-2-hydroxy-2-methyl-1-propane-1-one, 1-(4-(phenylthio)phenyl)-1,2-octanedione 2-(O-benzoyl oxime), 2-(acetoxyimino)-1-(4-(4-(2-hydroxyethoxy)phenylthio)phenyl)propane-1-one, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4-dimethylthioxanthen-9-one, and the like.
[0073] The preferred lower limit of the content of the photopolymerization initiator is 0.01 parts by mass, and the preferred upper limit is 10 parts by mass relative to 100 parts by mass of the curable resin. By making the content of the photopolymerization initiator within this range, the storage stability and photocurability of the obtained liquid crystal element sealant become more excellent. The more preferred lower limit of the content of the photopolymerization initiator is 0.1 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0074] The sealing agent for liquid crystal elements of the present invention contains a thermosetting agent.
[0075] Examples of the thermosetting agent include organic acid hydrazides, imidazole derivatives, amine compounds, polyphenol compounds, and acid anhydrides. Among them, organic acid hydrazides are preferably used.
[0076] Examples of the organic acid hydrazide include sebacic acid dihydrazide, isophthalic acid dihydrazide, adipic acid dihydrazide, and malonic acid dihydrazide.
[0077] Examples of commercially available organic acid hydrazides include organic acid hydrazides manufactured by Otsuka Chemical Co., Ltd., organic acid hydrazides manufactured by Ajinomoto Fine-Techno Co., Ltd., and organic acid hydrazides manufactured by Nippon Finechem Co., Ltd.
[0078] Examples of the organic acid hydrazide manufactured by Otsuka Chemical Co., Ltd. include SDH and ADH.
[0079] Examples of the organic acid hydrazide manufactured by Ajinomoto Fine-Techno include AJICURE VDH, AJICURE VDH-J, AJICURE UDH, and AJICURE UDH-J.
[0080] Examples of the organic acid hydrazide manufactured by Nippon Finechem Co., Ltd. include MDH and the like.
[0081] Relative to 100 parts by mass of the curable resin, the preferred lower limit of the content of the thermosetting agent is 1 part by mass, and the preferred upper limit is 50 parts by mass. By making the content of the thermosetting agent within this range, the obtained liquid crystal element sealant maintains storage stability, coating properties, and thermosetting properties are more excellent. The more preferred upper limit of the content of the thermosetting agent is 30 parts by mass.
[0082] The sealing agent for liquid crystal elements of the present invention preferably contains a filler for the purpose of increasing viscosity, improving adhesion due to a stress dispersion effect, improving a linear expansion coefficient, improving moisture resistance of a cured product, and the like.
[0083] As the filler, an inorganic filler or an organic filler can be used.
[0084] Examples of the inorganic filler include silica, talc, glass beads, asbestos, gypsum, diatomaceous earth, smectite, bentonite, montmorillonite, sericite, activated clay, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, aluminum hydroxide, aluminum nitride, silicon nitride, barium sulfate, and calcium silicate.
[0085] Examples of the organic filler include polyester microparticles, polyurethane microparticles, vinyl polymer microparticles, and acrylic polymer microparticles.
[0086] The above-mentioned fillers may be used alone or in combination of two or more.
[0087] The preferred lower limit of the content of the filler is 5 parts by mass, and the preferred upper limit is 30 parts by mass relative to 100 parts by mass of the curable resin. By making the content of the filler within this range, the effects of improving adhesion and the like are excellent without deteriorating the coating properties and the like. The more preferred lower limit of the content of the filler is 10 parts by mass, and the more preferred upper limit is 25 parts by mass.
[0088] The sealing agent for liquid crystal cells of the present invention preferably contains a silane coupling agent. The silane coupling agent mainly functions as an adhesion aid for favorably bonding the sealing agent for liquid crystal cells to a substrate or the like.
[0089] As the silane coupling agent, for example, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, etc. are preferably used.
[0090] Relative to 100 parts by mass of the curable resin, the preferred lower limit of the content of the silane coupling agent is 0.1 parts by mass, and the preferred upper limit is 10 parts by mass. By making the content of the silane coupling agent within this range, the occurrence of liquid crystal contamination is suppressed, and the effect of improving adhesion becomes more excellent. The more preferred lower limit of the content of the silane coupling agent is 0.3 parts by mass, and the more preferred upper limit is 5 parts by mass.
[0091] The sealing agent for liquid crystal elements of this invention may contain a light-shielding agent. By containing the said light-shielding agent, the sealing agent for liquid crystal elements of this invention can be used suitably as a light-shielding sealing agent.
[0092] Examples of the light-shielding agent include iron oxide, titanium black, aniline black, cyanine black, fullerene, carbon black, and resin-coated carbon black. Among them, titanium black is preferred.
[0093] The titanium black is a substance whose transmittance is increased near the ultraviolet region, especially the light with a wavelength of 370 nm or more and 450 nm or less, compared with the average transmittance for the light with a wavelength of 300 nm or more and 800 nm or less. That is, the titanium black is a light-shielding agent having the following properties: it imparts light-shielding properties to the liquid crystal element sealant of the present invention by fully shielding the light with a wavelength in the visible light region, and on the other hand, it transmits the light with a wavelength near the ultraviolet region. Therefore, as the above-mentioned photopolymerization initiator, by using a substance that can initiate a reaction using light with a wavelength (370 nm or more and 450 nm or less) that can increase the transmittance of the titanium black, the photocurability of the liquid crystal element sealant of the present invention can be further increased. In addition, as the light-shielding agent contained in the liquid crystal element sealant of the present invention, a substance with high insulating properties is preferably used, and titanium black is also suitable as a light-shielding agent with high insulating properties.
[0094] The optical density (OD value) per 1 μm of the titanium black is preferably 3 or more, more preferably 4 or more. The higher the light shielding property of the titanium black, the better. There is no particularly preferred upper limit for the OD value of the titanium black, but it is usually 5 or less.
[0095] The titanium black described above can fully exert its effect even without surface treatment, but titanium black whose surface has been treated with an organic component such as a coupling agent, titanium black coated with an inorganic component such as silicon oxide, titanium oxide, germanium oxide, aluminum oxide, zirconium oxide, magnesium oxide, etc., and titanium black that has been surface treated can also be used. Among them, titanium black treated with an organic component is preferred from the perspective of further improving insulation.
[0096] In addition, a liquid crystal display element produced using the sealing agent for a liquid crystal element of the present invention containing the titanium black as a light-shielding agent has sufficient light-shielding properties, and thus a liquid crystal display element having high contrast and excellent image display quality without light leakage can be realized.
[0097] As what is commercially available among the said titanium black, titanium black manufactured by Mitsubishi Materials Co., Ltd. and titanium black manufactured by Ako Chemical Co., Ltd. are mentioned, for example.
[0098] Examples of titanium black manufactured by Mitsubishi Materials include 12S, 13M, 13M-C, 13R-N, and 14M-C.
[0099] As the titanium black manufactured by Ako Chemicals Co., Ltd., for example, Tilack D etc. can be mentioned.
[0100] The preferred lower limit of the specific surface area of the titanium black is 13 m 2 / g, the preferred upper limit is 30m 2 / g, and a more preferred lower limit is 15m 2 / g, and the more preferred upper limit is 25m 2 / g.
[0101] The volume resistivity of the titanium black preferably has a lower limit of 0.5 Ω·cm, an upper limit of 3 Ω·cm, a more preferred lower limit of 1 Ω·cm, and a more preferred upper limit of 2.5 Ω·cm.
[0102] The primary particle size of the above-mentioned light-shielding agent is not particularly limited as long as it is below the distance between the substrates of the liquid crystal cell, and the preferred lower limit is 1nm, and the preferred upper limit is 5000nm. By making the primary particle size of the above-mentioned light-shielding agent be this range, it is possible to make the light-shielding property more excellent without deteriorating the coating property of the obtained liquid crystal cell sealant, etc. The more preferred lower limit of the primary particle size of the above-mentioned light-shielding agent is 5nm, the more preferred upper limit is 200nm, the further preferred lower limit is 10nm, and the further preferred upper limit is 100nm.
[0103] The primary particle size of the light-shielding agent can be measured by dispersing the light-shielding agent in a solvent (water, an organic solvent, etc.) using NICOMP 380ZLS (manufactured by PARTICLESIZING SYSTEMS Co., Ltd.).
[0104] Relative to 100 parts by mass of the above-mentioned curable resin, the preferred lower limit of the content of the above-mentioned light-shielding agent is 5 parts by mass, and the preferred upper limit is 80 parts by mass. By making the content of the above-mentioned light-shielding agent be the scope, the adhesion of the obtained liquid crystal element sealant, the strength after curing and the depiction property can not be greatly reduced, and the effect of improving light-shielding can be further exerted. The more preferred lower limit of the content of the above-mentioned light-shielding agent is 10 parts by mass, and the more preferred upper limit is 70 parts by mass, and the further preferred lower limit is 30 parts by mass, and the further preferred upper limit is 60 parts by mass.
[0105] The sealing agent for liquid crystal elements of the present invention may further contain additives such as a reactive diluent, a curing accelerator, a defoaming agent, a leveling agent, and a polymerization inhibitor as needed.
[0106] Examples of a method for producing the sealing agent for a liquid crystal element of the present invention include a method of mixing a curable resin, a thermal polymerization initiator, a photopolymerization initiator, a thermosetting agent, and other components such as an inorganic filler and a silane coupling agent using a mixer.
[0107] Examples of the mixer include a homodisperser, a homomixer, a universal mixer, a planetary mixer, a kneader, and a three-roll mill.
[0108] The preferred upper limit of the Martens hardness of the cured product of the liquid crystal element sealant of the present invention when measured by a nanoindenter is 180 MPa. By making the above-mentioned Martens hardness below 180 MPa, the stress relaxation property of the cured product obtained by the liquid crystal element sealant of the present invention becomes more excellent, and peeling can be further suppressed. The more preferred upper limit of the above-mentioned Martens hardness is 150 MPa.
[0109] In addition, although there is no particular limitation on the preferred lower limit of the Martens hardness of the cured product of the sealing agent for liquid crystal elements of the present invention when measured with a nanoindenter, the lower limit is substantially 1 MPa.
[0110] It should be noted that the Martens hardness is calculated from the load displacement curve obtained by using a nanoindenter at 25°C, a maximum load of 100 mN, and a depth of 800 nm to perform an indentation test using a Berkovich-type diamond indenter in accordance with ISO 14577. In addition, as a cured product for measuring the Martens hardness, a liquid crystal element sealant is irradiated with 100 mW / cm for 1 second. 2 After being irradiated with ultraviolet rays, the cured product was cured by heating at 80°C for 60 minutes.
[0111] The preferred upper limit of the indentation hardness (nanoindentation hardness) of the cured product of the liquid crystal element sealant of the present invention when measured by a nanoindenter is 30MPa. By making the above-mentioned indentation hardness below 30MPa, the stress relaxation of the cured product of the liquid crystal element sealant of the present invention becomes more excellent, and peeling can be further suppressed. The more preferred upper limit of the above-mentioned indentation hardness is 25MPa.
[0112] In addition, although there is no particular limitation on the preferred lower limit of the indentation hardness of the cured product of the sealing agent for liquid crystal elements of the present invention when measured with a nanoindenter, the lower limit is substantially 1 MPa.
[0113] It should be noted that the above-mentioned indentation hardness is a value calculated from a load displacement curve obtained by indenting a Berkovich-type diamond indenter at 25°C, a maximum indentation load of 100 mN, and an indentation depth of 800 nm using a nanoindenter in accordance with ISO14577. In addition, as a cured product for measuring the above-mentioned indentation hardness, a liquid crystal element sealant is irradiated with 100 mW / cm for 1 second. 2 After being irradiated with ultraviolet rays, the cured product was cured by heating at 80°C for 60 minutes.
[0114] Moreover, by mix|blending conductive fine particles in the sealing agent for liquid crystal elements of this invention, a vertical conduction material can be manufactured.
[0115] As the conductive particles, metal balls, conductive particles having a conductive metal layer formed on the surface of resin particles, etc. can be used. Among them, conductive particles having a conductive metal layer formed on the surface of resin particles are suitable because they can be electrically connected without damaging a transparent substrate, etc., due to the excellent elasticity of the resin particles.
[0116] The sealing agent for liquid crystal elements of this invention is used suitably as a sealing agent for liquid crystal cell frames for manufacture of a liquid crystal display element.
[0117] As a method for producing the above-mentioned liquid crystal display element using the sealing compound for liquid crystal elements of the present invention, a liquid crystal dropping process is preferably used, and specifically, for example, a method having the following steps can be mentioned.
[0118] First, a process of forming a frame-shaped seal pattern by applying the sealant for the liquid crystal element of the present invention on the orientation film of one of the two transparent substrates having electrodes such as ITO thin films and orientation films by screen printing, dispenser coating, etc. is performed. Next, a process of applying tiny droplets of liquid crystal to the entire surface of the frame of the seal pattern and overlapping another transparent substrate under vacuum is performed. After that, a process of pre-curing the sealant by irradiating the seal pattern portion with light such as ultraviolet rays (photocuring process) and a process of heating the pre-cured sealant to cure it (thermocuring process) is performed, thereby obtaining a liquid crystal display element.
[0119] Effects of the Invention
[0120] According to the present invention, it is possible to provide a sealing agent for a liquid crystal element which is excellent in low liquid crystal contamination properties when thermally cured at a low temperature and can suppress peeling after curing. DETAILED DESCRIPTION
[0121] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0122] (Examples 1 to 12, Comparative Examples 1 to 5)
[0123] The materials were stirred with a planetary stirring device according to the mixing ratios listed in Tables 1 and 2, and then uniformly mixed with a ceramic three-roll mill to obtain liquid crystal element sealing agents of Examples 1 to 12 and Comparative Examples 1 to 5. Awatori Rentaro (manufactured by THINKY Corporation) was used as the planetary stirring device.
[0124] In addition, the content ratio of ethylene oxide-added isocyanuric acid triacrylate in ARONIX M-315 of Tables 1 and 2 is 87 to 97% by mass.
[0125] The structures of the thermal polymerization initiators in Tables 1 and 2 are shown below.
[0126] V-65 (2,2′-azobis(2,4-dimethylvaleronitrile)) is a compound wherein R in the above formula (1) is a branched organic group having 4 carbon atoms.
[0127] V-70 (2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile)) is a compound wherein R in the above formula (1) is a branched organic group having 5 carbon atoms and containing an ether bond.
[0128] V-501 (4,4′-azobis(4-cyanovaleric acid)) is a compound wherein R in the above formula (1) is a linear organic group having 3 carbon atoms and containing a carboxyl group.
[0129] VPE-0201 (4,4′-azobis(4-cyanovaleric acid)-polyethylene glycol condensate) is a compound in which R in the above formula (1) is a linear organic group having 5 or more carbon atoms and containing an ester bond and an ether bond.
[0130] AIBN (2,2′-azobis(isobutyronitrile)) is a compound in which the portion corresponding to R in the above formula (1) is a linear organic group having 1 carbon atom.
[0131] V-59 (2,2′-azobis(2-methylbutyronitrile)) is a compound in which the portion corresponding to R in the above formula (1) is a linear organic group having 2 carbon atoms.
[0132] (Martens hardness and indentation hardness of cured product)
[0133] Each of the obtained sealing agents for liquid crystal elements was irradiated with a UV irradiator ("MB 1500T-3" manufactured by SEN LIGHTS) at 100 mW / cm2 for 1 second through a 340 nm cutoff filter. 2 After ultraviolet rays (wavelength 365nm), heated at 80°C for 60 minutes, a cured product with a thickness of 0.3mm was obtained. The cured product obtained was subjected to an indentation test of a Berkovich-type diamond indenter at 25°C, a maximum indentation load of 100mN, and an indentation depth of 800nm using a nanoindenter (ELIONIX, Inc., "ENT-2100") according to ISO14577. The Martens hardness and indentation hardness (nanoindentation hardness) were calculated from the load-displacement curve obtained. The results are shown in Tables 1 and 2.
[0134] <Evaluation>
[0135] The following evaluations were performed on the sealing agents for liquid crystal elements obtained in the examples and comparative examples.
[0136] (Low liquid crystal contamination when thermally cured at low temperatures)
[0137] To each obtained liquid crystal element sealant 100 parts by mass, add 1 part by mass of silica spacer, utilize planetary stirring device to make it evenly dispersed, carry out degassing treatment, remove the bubble in liquid crystal element sealant, fill in distribution syringe, carry out degassing treatment again.As silica spacer, SI-H055 (made by Sekisui Chemical Industry Co., Ltd.) is used, and as distribution syringe, PSY-10E (made by Musashi Engineering Co., Ltd.) is used.Then, using a dispenser, liquid crystal element sealant is applied to a glass substrate in the form of a depicting frame.As a dispenser, SHOTMASTER300 (made by Musashi Engineering Co., Ltd.) is used.Then, the tiny droplets of FFS liquid crystal are dripped and applied to the frame of liquid crystal element sealant with a liquid crystal drop device.On the glass substrate dripped with FFS liquid crystal, another glass substrate is overlapped across the liquid crystal element sealant, and two glass substrates are bonded under a reduced pressure of 5Pa with a vacuum bonding device to obtain a unit. As FFS liquid crystal, JC-5223XX (manufactured by Chisso Corporation) was used. The obtained cell was irradiated with 100 mW / cm2 for 1 second through a 340 nm cutoff filter using a UV irradiator (manufactured by SEN LIGHTS Corporation, "MB1500T-3"). 2 After irradiating with ultraviolet rays, the liquid crystal element was heated at 80°C for 60 minutes to cure the sealing agent for the liquid crystal element to produce a liquid crystal element.
[0138] The obtained liquid crystal element was confirmed for orientation disorder (display unevenness) using a polarizing microscope (Keyence Corporation, "VHX-5000"). Orientation disorder was determined by the color unevenness of the display part, and low liquid crystal contamination was evaluated in 5 stages from 1 to 5 according to the degree of color unevenness. The case where no color unevenness was observed in the liquid crystal element was set to "1", and the case where deep color unevenness was clearly confirmed was set to "5". The larger the number, the greater the orientation disorder. 5 is a level that is unsuitable for practical use.
[0139] (Anti-peeling property after curing)
[0140] Using each of the obtained sealing agents for liquid crystal elements, a liquid crystal element was produced in the same manner as in the above-mentioned "(Low liquid crystal contamination property during heat curing at low temperature)".
[0141] The obtained liquid crystal element was vibrated in water for 10 minutes using an ultrasonic cleaning machine (AS ONE, "VS-10003", 28kH conditions). The liquid crystal element after being vibrated by the ultrasonic cleaning machine was observed using an optical microscope (Keyence, "VHX-5000"), and the situation where the peeling of the substrate was not confirmed was set as "○", and the situation where the peeling of the substrate was confirmed was set as "×", and the anti-peeling property after curing was evaluated.
[0142] [Table 1]
[0143]
[0144] [Table 2]
[0145]
[0146] Industrial Applicability
[0147] According to the present invention, it is possible to provide a sealing agent for a liquid crystal element which is excellent in low liquid crystal contamination properties when thermally cured at a low temperature and can suppress peeling after curing.
Claims
1. A sealing agent for a liquid crystal element, characterized in that Contains curable resin, thermal polymerization initiator, photopolymerization initiator and thermal curing agent, The curable resin comprises a (meth)acrylic compound and an epoxy compound, The (meth)acrylic compound includes a compound having three or more (meth)acryloyl groups in one molecule. The thermal polymerization initiator is an azo compound having a cyano group and an azo group, At least one of the cyano group and at least one of the azo group are bonded to the same carbon atom, The carbon atom bonded to at least one of the cyano group and at least one of the azo group is further bonded to a linear or branched organic group having 3 or more carbon atoms.
2. The sealing agent for a liquid crystal element according to claim 1, wherein The (meth)acrylic compound includes a compound having four or more (meth)acryloyl groups in one molecule.
3. The sealing agent for liquid crystal elements according to claim 1 or 2, wherein The linear or branched organic group having 3 or more carbon atoms contains one or more oxygen atoms.
4. The sealing agent for liquid crystal elements according to claim 1 or 2, wherein The linear or branched organic group having 3 or more carbon atoms includes at least one polar group selected from the group consisting of a carboxyl group, an ester bond, and an ether bond.
5. The sealing agent for liquid crystal elements according to claim 1 or 2, wherein The cured product of the liquid crystal element sealing agent has a Martens hardness of 180 MPa or less when measured with a nanoindenter.
6. The sealing agent for liquid crystal elements according to claim 1 or 2, wherein The cured product of the liquid crystal element sealant has an indentation hardness of 30 MPa or less when measured with a nanoindenter.
Citation Information
Patent Citations
Sealing agent for dropping process of LCD panel
JP2001133794A
Curing resin composition and sealants and end-sealing materials for displays
WO2002092718A1